Lithic Assemblages of the Linear Pottery Culture Settlement Modrychi-I - Telizhenko, S.A.; Silaiev, O.M. (Археологія, 2022)
A total of 145 flint items, as well as four obsidians and seven stone-made artefacts, were collected during the excavations on the Linear Pottery culture settlement Modrychi-1 in Lviv Oblast, which is located within Ukrainian Outer Subcarpathia. The assemblage of flint and obsidian items has been analyzed as an integral complex that characterizes the material culture of the Neolithic settlement. The prevailing number of flint items such as cores, flakes and blades reflect on-site production. As for the obsidian artefacts, an attempt was made to establish the origin of raw materials.